Study the pathological changes and the bacterial and parasitic agents present in some internal organs of wild rats.: Mohammed J. Alwan , Haider M. Ali and Sanaria F. Al- Hissen - Alwan, Mohammed J. (The Iraqi Journal of Veterinary Medicine, 2005)
In order to study the pathological lesion in some internal organs of wildrats as well as bacteriological and parasitic isolation. Post-mortom examinationof 45 wild rats collected from different parts of baghdad city was done. The rsultshowed that 29 rats from 45 were infected with Cryptosporidia spp , andHymenolips spp . Bacteriological and pathological examination revealed thefollowing bacterial Isolate and pathological changes :1. Sub acute suppurative hepatitis , Klebisella spp, Salmonella typhimuriumwere isolated from this lesion .2. Granulomatus hepatitis with isolates of Ps.aeroginosa , E. coli and Kl.spp.3. Acute Fibrinous pericarditis with isolates of Ps. Aeruginosa, Strep.Pyogens.4. Nephrosis .5. Subacute suppurative entritis , with S. typhimurium and Cryptospordia spp .isolates.6. Parasitic entritis .Cryptosporidia spp. and Hymenolips spp were isolated frominfected tract .7. Acute Hepatocellular degenration with bacterial isolates included Staph.aureus and proteus spp.